Natural activators of autophagy reduce oxidative stress and muscle injury biomarkers in endurance athletes: A pilot study - D'Amico, A.; Fossati, C.; Pigozzi, F.; Borrione, P.; Peruzzi, M.; Bartimoccia, S.; Saba, F.; Pingitore, A.; Biondi-Zoccai, G.; Petramala, L.; De Grandis, F.; Vecchio, D.; et al. (Nutrients, 2023)
Background: Oxidative stress and impaired autophagy are directly and indirectly implicated in exercise-mediated muscle injury. Trehalose, spermidine, nicotinamide, and polyphenols possess pro-autophagic and antioxidant properties, and could therefore reduce exercise-induced damage to skeletal muscle. The aim of this study was to investigate whether a mixture of these compounds was able to improve muscle injury biomarkers in endurance athletes through the modulation of oxidative stress and autophagic machinery. Methods and Results: sNOX2-dp; H2O2 production; H2O2 breakdown activity (HBA); ATG5 and p62 levels, both markers of autophagic process; and muscle injury biomarkers were evaluated in five endurance athletes who were allocated in a crossover design study to daily administration of 10.5 g of an experimental mixture or no treatment, with evaluations conducted at baseline and after 30 days of mixture consumption. Compared to baseline, the mixture intake led to a remarkable reduction of oxidative stress and positively modulated autophagy. Finally, after the 30-day supplementation period, a significant decrease in muscle injury biomarkers was found. Conclusion: Supplementation with this mixture positively affected redox state and autophagy and improved muscle injury biomarkers in athletes, allowing for better muscle recovery. Moreover, it is speculated that this mixture could also benefit patients suffering from muscle injuries, such as cancer or cardiovascular patients, or elderly subjects.